Radio Rookies - Sample CD
Audio recordings of WNYC Radio Rookies in which New York City teenagers tell their stories and take the listeners inside their lives and their communities. The stories include: “President” by Jiovan Ortiz; “Heroin” by Janesse Nieves; “Poetry – Bushwick, Brooklyn” by Judith Rudge; “Dropping Out” by Rafael Lopez; “Suicide” by Linda Cuevas; “English” by Karla Saavedra; “Guns – Harlem, Manhattan” by Jesus Gonzales; “Pirate Radio” by Antoine Bazilio; “Trisomy 13” by Marc Delgado.